HISTORICAL PERSPECTIVE and HUMAN CONSEQUENCES of AFRICANIZED BEE STINGS IN THE AMERICAS - Ferreira, R. S. [UNESP]; Almeida, Ricardo Augusto Monteiro de Barros [UNESP]; Barraviera, Silvia Regina Catharino Sartori [UNESP]; Barraviera, Benedito [UNESP] (Taylor & Francis Inc, 2012)
In 1956, Africanized bees began to spread in the American continent from southern Brazil, where original African bees mated with European bees. A few years later, in 1990, these Africanized bees reached the United States and were found in Texas. Currently, these hybrid bees are found in several North American states and will probably reach the Canadian border in the future. Although the presence of Africanized bees had produced positive effects on Brazilian economy, including improvement in crop pollination and in honey production, turning Brazil into a major exporter, the negative impacts-such as swarming, aggressive behavior, and the ability to mass attack-resulted in serious and fatal envenomation with humans and animals. Victims of bee attacks usually develop a severe envenomation syndrome characterized by the release of a large amount of cytokines [interleukins (IL) IL-1, IL-6, IL-8], and tumor necrosis factor (TNF). Subsequently, such cytokines produce an acute inflammatory response that triggers adverse effects on skeletal muscles; bone marrow; hepatic and renal functions; and cardiovascular, central nervous, and immune systems. Finally, the aim of the present review is to study historical characteristics and current status of Africanized bees' spread, the composition of their venom, the impact of the bees on the Brazilian economy and ecology, and clinical aspects of their stings including immune response, and to suggest a protocol for bee sting management since there is no safe and effective antivenom available.